Lycopodium clavatum exine microcapsules enable safe oral delivery of 3, 4-diaminopyridine for treatment of botulinum neurotoxin A intoxication. Issue 22 (24th February 2016) - Harris, T. L.; Wenthur, C. J.; Diego-Taboada, A.; Mackenzie, G.; Corbitt, T. S.; Janda, K. D.
Abstract : Biopolymeric spores and shellac can be rapidly employed to generate a scalable, pH-dependent, controlled-release microcapsule delivery system. Abstract : 3, 4-Diaminopyridine has shown promise in reversing botulinum intoxication, but poor pharmacokinetics and a narrow therapeutic window limit its clinical utility. Thus, we developed a pH-dependent oral delivery platform using club moss spore exines. These exine microcapsules slowed 3, 4-diaminopyridine absorption, limited its seizure activity, and enabled delivery of doses which prolonged mouse survival after botulism neurotoxin A intoxication.